Efektivitas Model Pembelajaran TSTS (Two Stay Two Stray) Terhadap Hasil Belajar IPA Siswa SD - I Putu Windu Pratama; Ign. Wayan Suwatra; I Made Citra Wibawa (Universitas Pendidikan Ganesha, 2021)
There have been many studies examining the effect of the two stay two stray learning model on the science learning outcomes of elementary school students, but the results of these studies have not received further studies to summarize and retest the effectiveness of the effect of the learning model used. This study aims to determine the effect of the two stay two stray learning models on the science learning outcomes of elementary school students. This research is library research with a meta-analysis data analysis technique. The subject of this research is a research article totaling 13 articles from various Sinta accredited research journals. Data collection using the library study technique was continued by conducting a study on articles related to the research topic. The data that has been obtained is reprocessed using quantitative methods. Based on the results of the analysis of the use of the two stay two stray learning models in learning, it is proven that it can improve student learning outcomes, the lowest is 0.41 and the highest is 2.67. Based on the results of the study, it can be concluded that the Two Stay Two Stray learning model can improve students' science learning outcomes in the experimental group which is larger than the control group. This shows that the Two Stay Two Stray learning model has an effective influence on science learning.